1996
DOI: 10.1007/bf00031820
|View full text |Cite
|
Sign up to set email alerts
|

A survey of toxicity of cyanobacterial blooms in Lake Ladoga and adjacent water bodies

Abstract: Twentyfive cyanobacterial blooms in Lake Ladoga and adjacent water bodies were studied in the summer of 1990-1992 . Toxicity of the water bloom material for mice was detected in 9 cases . The maximal tolerable doses (MTD) of the material extracted from biomass varied within 3-30 mg kg -1 mouse body weight; 50% lethal doses (LD5o) were within 45-125 mg kg -1 . Toxic water blooms were registered in Karelian lakes and in the Neva Bay, Gulf of Finland . Cyanobacterial samples collected on the eastern coast of Lake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Russia possesses the world's second renewable water reserves after Brazil [13]. A significant number of scientific publications as well as reports in the mass media show that the problem of eutrophication is widespread in Russia [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Russia possesses the world's second renewable water reserves after Brazil [13]. A significant number of scientific publications as well as reports in the mass media show that the problem of eutrophication is widespread in Russia [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research indicates that G. echinulata may contain toxins. Cronberg (1999) and Cronberg et al (1999) established that recreational human exposure to G. echinulata blooms in Lake Ringsjön, Sweden can create skin irritation, and Gromov et al (1996) found that injections of G. echinulata isolated from Lake Ladoga, Russia, were fatal to mice. G. echinulata is in the order Nostocales and family Rivulariaceae (Prescott, 1973), and toxicity surveys of phylogentically-related cyanobacteria such as Aphanizomenon and Nostoc (Dos S Vieira et al, 2005) suggest that G. echinulata may contain the hepatotoxin microcystin.…”
Section: Introductionmentioning
confidence: 99%